Open Educational Resources in the Time of COVID-19: Two Case Studies of Open Video Design in the Remote Learning Environment - Doi, Carolyn; Lucky, Shannon; Rubin, Joseph E. (KULA)

(untitled) (University of Victoria Libraries, 2022)
The COVID-19 pandemic caused many post-secondary institutions to close abruptly in early 2020, and instructors were expected to transition to remote online instruction with little notice. For many instructors, hastily recorded lecture-capture videos alongside digital slides became the default mode of sharing instructional content. This sudden shift to video-based instruction was a significant challenge but also presented an opportunity to develop some instructional videos as open educational resources (OER). This paper outlines two case studies from the University of Saskatchewan in which a mix of OER and class-specific, closed-content videos were designed and integrated into remote learning environments. In designing these videos, we focused on technical design elements and accessibility, ability to reuse and share, and student engagement. Both cases, one in veterinary microbiology and the other in music research methods, followed similar strategies for creating multiple types of video content for the course, focusing on four distinct types (labs and demonstrations, guest interviews, lectures, and course information). Choosing to develop and share some of this video content as OER allowed us to expand the use of these learning objects beyond the online classroom. We discuss our considerations for making some videos open, including novelty of the content, reusability, copyright, privacy, and demands on instructor time. We also provide an introduction to our production process and practical tips, including planning, audiovisual production, editing, accessibility, and sharing platforms. The COVID-19 closures made 2020 an unexpectedly challenging year for students and instructors, but the necessity of moving instruction online prompted us to focus on supporting students in this new environment and helped us contribute to the growing body of OER.